TRANSFORMASI DIGITAL DAN DESAIN KEMASAN: MENGUATKAN AKSES PASAR PRODUK KELOMPOK WANITA TANI SOMOSARI - Aisa Mei Safara; Rizki Salam Noahdian; Santi Andriyani (Universitas Mataram, 2024)
Somosari Village Women Farmers Group (KWT) faces challenges in improving market access and competitiveness of their products such as coffee and dried oranges. Limitations in digital marketing and unattractive packaging design cause these products to be less recognized in the wider market. This service activity aims to implement digital transformation strategies and packaging design development so that KWT Somosari products can be more accessible and have higher appeal. The methods used include redesigning product design and packaging, digital marketing training, training in the application of e-commerce technology and assistance in the halal certification process. The results of this activity showed an increase in KWT members' knowledge of digital marketing, as well as improved packaging design that successfully increased product attractiveness. Increased sales were also seen from wider access to online markets. In conclusion, digital transformation and packaging design innovation proved effective in strengthening the market access and competitiveness of KWT Somosari products.